How Reliable Is the Market for Technology? - Palermo, Vincenzo; Higgins, Matthew J.; Ceccagnoli, Marco (The Review of Economics and Statistics, 2019)
Research has focused on why and when firms access external technology markets. Less is known about the reliability of patents attached to licensed technologies during litigation. Unreliable patents expose a firm to loss of downstream revenues. We address this by constructing a data set of patent litigation in the pharmaceutical industry and exploit a change in patent law that exogenously increased the probability of litigation. We find that licensed patents are more likely to fall during litigation. This effect is isolated to firms with fewer intellectual property capabilities and less patenting experience, suggesting that benefits from external technology are not shared equally.